THE PODIFORM CHROMITE AND PLATINUM GROUP ELEMENTS IN THE NEOPROTEROZOIC OPHIOLITE BOU AZZER (INLIER BOU AZZER - EL GRÂARA, CENTRAL ANTI-ATLAS) - A., Wafik; M., Bhilisse; H., Admou; L., Maacha; M., Elghorfi; M., Constantin (European Scientific Journal, ESJ, 2015)
Chromite deposits associated with ophiolites Bou Azzer correspond to podiform chromitites concentrated in the eastern part of the inlier Bou Azzer -El Grâara. They appear as small diamond-shaped body oriented and they cross a fracture system reflecting their implementation mode. Tectonics which affects the body is polyphase. Synchronous phase of their implementation is transtensive. This is evidenced by the forms of “pullaparts” common to the pods and breccia textures. Also, this was observed in metallographic microscope and SEM (scanning electron microscope), and earlier in serpentinization. This tectonic would also control the dyking system to which chromitite pods are associated. The distribution of the deposits along the inlier Bou Azzer shows a regional zonation, western chrome enrichment (52% Cr2O3), and a loss to the east (30% Cr2O3). The massive chromite is the chromite with a 62% in Cr2O3 and with enrichment in magnesium and trivalent iron depletion. Disseminated chromite can be divided into two types. The disseminated chromite podiform which is similar to the massive chromite geological context and the setting mode is relatively poor with Cr2O3 contents below 50%. The second type includes chromite and chromospinelles which are scattered in serpentine and in association with sulphides and nickel arsenides. It is by far the most widespread, but has an average content of 14%. Chromitites Bou Azzer are characterized by a low ratio [P-EL / I-PGE] typical ophiolitic chromitites alpine poor in sulfides, with predominance of IPGE, variable contents of Rh, and low levels of Pt and Pd. The sum of the contents (PGE) chromitites of Inguejem Aït-Ahmane is about 187-221 ppb. The microprobe analysis shows that the unaltered chromites Bou Azzer have little variable composition and are not aluminous Cr / Al> 1. The Cr2O3 content is high and ranges from 55.85 to 58.85%, while the TiO2 content is less than 0.20%, which allows them to be placed in the area of rich chromites Cr and poor chromites Ti.